PENGARUH PERSEPSI TENTANG SANKSI PERPAJAKAN DAN KESADARAN WAJIB PAJAK PADA KEPATUHAN PELAPORAN WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA DENPASAR TIMUR - Muliari, Ni Ketut; Ery Setiawan, Putu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 1 (2011))
Tax revenue has been the most substantial source of government incomerecently. In 2009, about 73 percent of government revenue came from taxes. Thisforces taxation office to perform some efforts to maximize tax revenue. One of them isto employ self assessment system. In this system, taxpayer’s awareness andcompliance is important. Factors influencing taxpayer’s compliance includetaxpayer’s perception of tax penalty and taxpayer’s awareness.This research aims to examine the effect of perception of tax penalty and taxawareness on taxpayer’s compliance in taxation office Pratama Denpasar Timur.Sample is drawn using simple random sampling method, and consists of 100effective taxpayers as respondents. Data then are analyzed using multiple linearregression technique. The result shows that perception of tax penalty and taxpayer’sawareness simultaneously affects taxpayer’s compliance with adjusted R-square of0.498. Partially, the two variables provide significant positive effect on taxpayer’scompliance.
Keywords: perception, tax penalty, tax awareness, compliance